Learners’ metacognitive strategies amid machine translation post-editing practices: An Indonesian EFL context - Tandiana, Soni Tantan; Abdullah, Fuad; Andriani, Agis; Rosmala, Dewi; Maakafi, Noha; Hikmatullah, Nanak (UPT Bahasa Universitas Tanjungpura, 2026)
The rapid advancement of information, communication and technology (ICT) has revolutionised translation from translating from scratch (TfS) to machine translation (MT). However, little research has been addressed on how learners apply metacognitive strategies while performing Machine Translation Post-editing (MTPE). As a result, this study was intended to fill this void. Five learners of the English Education Department were involved as investigative participants. The data were gathered through Zoom-mediated Think Aloud Protocols (TAP) as audiovisual recordings of the think-aloud activities, transcript of TAP results and the input event loggings. They were analysed using Arndt's categories of ESL writing strategies, which covered planning, global planning, rehearsing, repeating, rereading, questioning, revising, and editing (Arndt, 1987; Mu, 2005). The findings reported that the learners adopted relatively similar metacognitive strategies while practising MTPE both in English-Indonesian output and Indonesian-English output, except for global planning. In particular, they applied editing (44,2%), rereading (24,1%), repeating (14%), rehearsing (10,4%), questioning (7,1%), revising (0,9%), and planning (0,3%). Given these facts, metacognitive strategies in MTPE practices allow learners to produce more accurate and contextual translation output generated by MTs (e.g. Google Translate, DeepL etc.) and foster high-order thinking skills, self-regulatory strategies and motivation.